Central-wavelength-tunable multi-wavelength fiber laser based on micro-air gap cavity and tapered fiber structure. (24th July 2017) - Chen, Jiao; Tong, Zhengrong; Yang, He; Zhang, Weihua; Xue, Lifang; Pan, Honggang
Abstract: A multi-wavelength erbium-doped fiber laser based on a micro-air gap cavity filter and the tapered fiber structure is proposed and demonstrated. The micro-air gap cavity filter is constructed by aligning two polished single mode fiber facets carefully through a capillary. Then a tapered fiber structure is applied to compose a cascaded filter with the micro-air gap cavity filter. According to the experiment, the transmission spectrum of the tapered fiber structure acts as the outer envelope of the cascaded structure, which is used as a tunable filter. Moreover, the periodically localized peaks of the tapered fiber structure are modulated by sinusoidal spectral response of the micro-air gap cavity filter. And the micro-air gap cavity filter acts as a comb filter, which determines the channel space of the cascaded filter structure. By using the above superimposed filter, four wavelengths with a wavelength spacing of about 1.20 nm are generated under the pump power of 270 mW. The side-mode suppression ratio of all lasing wavelengths is about 35 dB. The tapered fiber structure is fixed on a furnace, when the temperature varies from 30 °C to 120 °C, the first wavelength can be tuned within the range of 5.31 nm.